The Cost Competitiveness of Manufacturing in China and India: An Industry and Regional Perspective - Bart van Ark (Indian Council for Research on International Economic Relations (ICRIER), 2008)
This paper focuses on comparisons of productivity, (unit) labor cost and industrylevel competitiveness for the manufacturing sector of China and India. We first provide a comparison between India and China using a broad international perspective. We find that China has increased its labor productivity to a level above that of India, but due to a somewhat higher compensation level, China is still somewhat at a disadvantage in terms of unit labor cost in manufacturing relative to India. In the second half of the paper, we make an analysis of industry level differences in productivity, labor compensation and unit labor costs at state and province level in the two countries from the mid 1990s to the early 2000s. We find rapid declines in unit labor cost across industries and provinces in China, but increases in many instances in India. This suggest that productivity and compensation growth have become much more aligned across regions in China whereas this is not (yet) the case in India. We relate these results to differences in the implementation of market reforms between the two countries and removal of barriers to resource mobility eradicating inefficient manufacturing activity.
Keywords: O14; J24; 330; cost competitiveness; manufacturing; India; China; labor productivity; Globalisierung; Wirtschaftswachstum; Wettbewerb; Produktionskosten; Industrie; Entwicklung; China; Indien